Supracricoid Laryngectomy: The Function of the Remaining Arytenoid in Voice and Swallowing - Buzaneli, Elaine Cristina Pires; Zenari, Marcia Simões; Kulcsar, Marco Aurélio Vamondes; Dedivitis, Rogerio A.; Cernea, Cláudio Roberto; Nemr, Kátia (International Archives of Otorhinolaryngology, 2018)
Introduction Supracricoid laryngectomy still has selected indications; there are few studies in the literature, and the case series are limited, a fact that stimulates the development of new studies to further elucidate the structural and functional aspects of the procedure.Objective To assess voice and deglutition parameters according to the number of preserved arytenoids.Methods Eleven patients who underwent subtotal laryngectomy with cricohyoidoepiglottopexy were evaluated by laryngeal nasofibroscopy, videofluoroscopy, and auditory-perceptual, acoustic, and voice pleasantness analyses, after resuming oral feeding.Results Functional abnormalities were detected in two out of the three patients who underwent arytenoidectomy, and in six patients from the remainder of the sample. Almost half of the sample presented silent laryngeal penetration and/or vallecular/hypopharyngeal stasis on the videofluoroscopy. The mean voice analysis scores indicated moderate vocal deviation, roughness and breathiness; severe strain and loudness deviation; shorter maximum phonation time; the presence of noise; and high third and fourth formant values. The voices were rated as unpleasant. There was no difference in the number and functionality of the remaining arytenoids as prognostic factors for deglutition; however, in the qualitative analysis, favorable voice and deglutition outcomes were more common among patients who did not undergo arytenoidectomy and had normal functional conditions.Conclusion The number and functionality of the preserved arytenoids were not found to be prognostic factors for favorable deglutition efficiency outcomes. However, the qualitative analysis showed that the preservation of both arytenoids and the absence of functional abnormalities were associated with more satisfactory voice and deglutition patterns.
Keywords: head and neck neoplasms; laryngectomy; voice; deglutition; speech therapy